2011
DOI: 10.1177/1534765610395614
|View full text |Cite
|
Sign up to set email alerts
|

Potentially traumatic events in a transgender sample: Frequency and associated symptoms.

Abstract: The frequency of potentially traumatic events (PTEs) and associated symptoms were examined in a cross-sectional study of 97 transgender participants who had been classified as male at birth. A total of 98% reported at least one PTE and 91% endorsed multiple events. Of those with PTE exposures, 42% reported that at least one event was transgender bias-related. Among those with PTEs, 17.8% endorsed clinically significant symptoms of PTSD and 64% reported clinically significant depressive symptoms. The percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 73 publications
10
92
0
Order By: Relevance
“…As part of a larger study (Shipherd, Green, & Abramovitz, 2010;Shipherd et al, 2011), anonymous survey packets were distributed and completed at a table in the vendor area of the conference hotel, as approved by the VA Boston Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of a larger study (Shipherd, Green, & Abramovitz, 2010;Shipherd et al, 2011), anonymous survey packets were distributed and completed at a table in the vendor area of the conference hotel, as approved by the VA Boston Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…As such, transgender-specific program development and training in cultural competence are salient for all providers in the VA (Maguen et al, 2005;Mizock & Lewis, 2008;Shipherd et al, 2010), particularly given the recent VA policy, which includes the provision of mental health care and preoperative evaluations (Department of Veterans Affairs, 2011). Training and provider awareness will be central features of education initiatives, given the elevated rates of suicide (Maguen & Shipherd, 2010), risk for HIV infection (Kenagy & Hsieh, 2005), exposure to trauma (Shipherd et al, 2011), and other health challenges in the transgender population. Mental and medical health services are potential points of intervention with transvets at risk, and properly trained and bias-free professionals are crucial in this endeavor.…”
Section: (12%) 2 (5%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on health issues within transgender populations largely focuses on HIV/AIDS, suicide, violence, and abuse (Kenagy, 2005;Shipherd, Maguen, Skidmore, & Abramovitz, 2010). These are important issues to study, yet they do not provide a full clinical picture.…”
Section: Introductionmentioning
confidence: 99%
“…Transgender people, who have a gender identity that differs from their assigned sex at birth, experience high levels of prejudice, discrimination, and violence (Bockting, Miner, Romine, Hamilton, & Coleman, 2013; Grant, 2011; Lombardi, Wilchins, Priesing, & Malouf, 2002; Mizock & Lewis, 2008; Shipherd, Maguen, Skidmore, & Abramovitz, 2011). A national study of more than 6,000 U.S. transgender respondents found that 63% reported an emotionally- or life-impairing experience of discrimination (Grant, 2011).…”
mentioning
confidence: 99%